Unhoming Homeland: Jewish Diaspora and Neturei Karta Community - C. Epafras, Leonard (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
Neturei Karta is a Jewish group that usually considered belongs to larger ‘ultra-Orthodox’ Judaism. This group established its community in Jerusalem since early 19th century, but never acknowledges the modern state of Israel and its administration. Its members never take Israeli Shekel notes, never join the Army Reserve, which is compulsory for adult Israeli, never sing Israel’s national anthem, never celebrate Israel Independence Day, and never set foot to the holiest place in the Judaism, the Wailing Wall – but they pay taxes to the state they hate so much. This paper explores the nature of this group and its position against Zionism. The main focus is about their anti-Zionism ideology in connection with the notion of Jewish ‘homeland’ and ‘diaspora’. Neturei Karta is a transnational religious phenomenon. It may differ from other transnational religious groups in its challenge to Zionism on the issues of ‘(Jewish) homeland’ and ‘Jewish diaspora’. This dissident voice within the Jewish history is deemed important to reassess the the exercise of power by Israeli in dominating and colonizing the Other, the Palestinians. Keywords :*Jewish, *Judaism, *Zionism, *anti-Zionism, *ideology, *diaspora, *homeland, *ultra-orthodox, *exile, *holy land, *promised land, *chosen people, *alienation, *geopiety, *'hyphenated' Jews